Reconstruction of Rights Based AI Governance: Right to Explanation Against Algorithmic Discrimination in ASEAN - Lisa Indahsari; Vebri Wulandari; Syafri Hariansyah (Referendum : Jurnal Hukum Perdata dan Pidana, 2026)
The rapid proliferation of artificial intelligence across Southeast Asia carries profound implications for the  protection of fundamental human rights, particularly as algorithmic discrimination becomes increasingly  embedded within automated decision making systems spanning public and private sectors alike. Although  several ASEAN member states have issued AI ethics guidelines, the prevailing soft law framework has  demonstrably failed to provide meaningful, enforceable protection for individuals subjected to biased and  opaque algorithmic decisions. This study aims to critically examine the extent to which existing AI ethics  guidelines in ASEAN fall short in mitigating algorithmic discrimination risks, and to reconstruct AI governance  policy through the formal recognition of the right to explanation as a binding human rights protection  instrument. Employing a normative juridical methodology, the research integrates a statute approach,  comparative legal analysis, and conceptual framework analysis to systematically evaluate current regulatory  inadequacies. The findings reveal that ASEAN's AI ethics guidelines remain largely voluntary, lack enforceable  accountability mechanisms, and fundamentally fail to meet adequate standards of algorithmic accountability.  A rights based reconstruction centered on the right to explanation anchored by a human understandable  explanation standard as a prerequisite for the legitimacy of automated decisions represents a transformative  normative shift from soft law to rights based AI governance. This study urges ASEAN to adopt a binding  regional AI regulatory framework that guarantees accountability, transparency, and the protection of citizens'  fundamental rights in the age of automation.